PENINGKATAN KEMAMPUAN BERPIKIR LOGIS DENGAN MENGGUNAKAN METODE PEMBELAJARAN KOOPERATIF TIPE TEAM-ACCELERATED INSTRUCTION - Dwi Maulida Sari; Rizky Nurul Hafni (Mahesa Research Center, 2020)
This study is a quasi-experimental study with a pretest-posttest one group design. The population in this study is all students majoring in mathematics education at an Asahan University, North Sumatra. Sampling was done by using the purposive sampling technique. Students work under the cooperative learning method Team-Accelerated Instruction (TAI) type. This research was conducted to study the enhancement of students’ logical thinking ability after cooperative learning TAI types were implemented. The instruments used in this study are logical thinking ability tests, observation sheets, and student interviews. The data were analyzed by using t-test. From the result of data analysis, it is found that there is a significant enhancement in the logical thinking ability of the students’ who work under the cooperative learning method TAI type. Therefore, cooperative learning Team-Accelerated Instruction (TAI) type can be alternative learning to improve students’ logical thinking ability.